Differential expression of Glycerol-3-Phosphate Dehydrogenase isoforms in flight muscles of the Chagas disease vector Triatoma infestans (Hemiptera, Reduviidae) - Stroppa, Maria Mercedes (2013)
Flight muscles of Triatoma infestans have two glycerol-3-phosphate dehydrogenase (GPDH) isoforms: GPDH-1 is involved in flight metabolism and GPDH-2 provides lipid precursors. Total GPDH activity was greater in the natural population and almost only due to GPDH-1. Different expression and activity observed between GPDH isoforms in the natural population and the first laboratory generation was not detected in the second laboratory generation. This pattern may be caused by gradual adaptation to laboratory nutritional conditions. During development, the expression of GPDH-2 increased with a longer time of intake, which would imply an increment in lipid biosynthesis. The GPDH-1 transcript predominated with respect to that of GPDH-2 in the lower nutritional condition, suggesting the necessity of insects to fly during this nutritional status. The transcriptional pattern showed a delay at 22°C. The isoforms activities and transcript patterns in flight muscles suggest transcriptional adaptation to metabolic requirements originated by alternative splicing.